A MINIMAL-INVASIVE METHOD TO RETRIEVE AND IDENTIFY ENTHESEAL TISSUE FROM PSORIATIC ARTHRITIS PATIENTS - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Soare, A.; Bräuer, Lars; Rech, Jürgen; Simon, David; Kleyer, Arnd; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Anatomy and physiology of the nasolacrimal ducts - Paulsen, Friedrich; Garreis, Fabian; Schicht, Martin; Bräuer, Lars; Ali, M. J.; Sel, Saadettin (HNO, 2016)
Ophthalmologists and interventional radiologists are not the only professionals for whom diseases of the efferent tear duct system occupy centre stage; this applies also to ENT specialists involving endonasal conservative or surgical treatment. On the basis of current knowledge and taking account of results yielded by own research in recent years and of clinical aspects, we here give an overview of basic knowledge on the anatomy and physiology of the nasolacrimal system. In doing so functional aspects regarding tear transport as well as embryological and pathophysiological issues are integrated.
EVALuna2:34492

Anatomy in times of pandemia – Impact on teaching and body donations - Tschernig, Thomas; Bechmann, Ingo; Meier, Carola; Paulsen, Friedrich; Waschke, Jens; Westermann, Jürgen; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2021)
CRIS-Team Scopus Importer:2021-09-03
Keywords: Anatomy; Body donations; Dissection courses; SARS-CoV-2; Teaching

A New Immortalized Human Lacrimal Gland Cell Line - Gleixner, Sophie; Zahn, Ingrid; Dietrich, Jana; Singh, Swati; Drobny, Alice; Schneider, Yanni; Schwendner, Raphael; Socher, Eileen; Blavet, Nicolas; Bräuer, Lars; Gostian, Antoniu-Oreste; Balk, Matthias; et al. (Cells, 2024)
The lacrimal gland is crucial for maintaining ocular health by producing the aqueous component of the tear film, which hydrates and nourishes the ocular surface. Decreased production of this component results in dry eye disease, a condition affecting over 250 million people worldwide. However, the scarcity of primary human material for studying its underlying mechanisms and the absence of a cell model for human lacrimal gland epithelial cells present significant challenges. Here, we describe the generation of immortalized human lacrimal gland cell lines through the introduction of an SV40 antigen. We successfully isolated and characterized three cell clones from a female lacrimal gland donor, confirming their epithelial identity through genomic and protein analyses, including PCR, RNAseq, immunofluorescence and cultivation in a 3D spheroid model. Our findings represent a significant advancement, providing improved accessibility to investigate the molecular pathogenesis mechanisms of dry eye disease and potential therapeutic interventions. We identified the expression of typical epithelial cell marker genes and demonstrated the cells’ capability to form 2D cell sheets and 3D spheroids. This establishment of immortalized human lacrimal gland cells with epithelial characteristics holds promise for future comprehensive studies, contributing to a deeper understanding of dry eye disease and its cellular mechanisms.<br
Keywords: lacrimal gland; epithelial cells; immortalized; cell line; dry eye; tears; tear secretion

Articular cartilage chondrocytes express aromatase and use enzymes involved in estrogen metabolism - Schicht, Martin; Ernst, Jana; Nielitz, Andrea; Fester, Lars; Tsokos, Michael; Guddat, Saskia S.; Bräuer, Lars; Bechmann, Judith; Delank, Karl-Stefan; Wohlrab, David; Paulsen, Friedrich; Claassen, Horst (Arthritis Research & Therapy, 2014)
Sex hormones, especially estrogens, have been implicated in articular cartilage metabolism and the pathogenesis of postmenopausal osteoarthritis. The conversion by aromatase (CYP19A1) of androstenedione into estrone (E1) and of testosterone into 17?-estradiol (E2) plays a key role in the endogenous synthesis of estrogens in tissue.We analyzed the expression of aromatase (CYP19A1) in immortalized C-28/I2 and T/C-28a2 chondrocytes, as well as in cultured primary human articular chondrocytes and human articular cartilage tissue, by means of RT-PCR, Western blotting and immunohistochemistry. By means of quantitative RT-PCR and enzyme-linked immunosorbent assay, we also determined whether the aromatase inhibitor letrozole influences estrogen metabolism of cultured chondrocytes in immortalized C-28/I2 chondrocytes.Aromatase mRNA was detected in both immortalized chondrocyte cell lines, in cultured primary human chondrocytes, and in human articular cartilage tissue. By means of Western blot analysis, aromatase was detected at the protein level in articular cartilage taken from various patients of both sexes and different ages. Cultured primary human articular chondrocytes, C-28/I2 and T/C-28a2, and human articular cartilage tissue reacted with antibodies for aromatase. Incubation of C-28/I2 chondrocytes with 10?¹¹ M to 10??M letrozole as an aromatase inhibitor revealed significantly increased amounts of the mRNAs of the enzyme cytochrome P4501A1 (CYP1A1), which is involved in the catagen estrogen metabolism, and of the estrogen receptors ER-? and ER-?. Concomitantly, synthesis of estrone (E1) was significantly downregulated after incubation with letrozole.We demonstrate that human articular cartilage expresses aromatase at the mRNA and protein levels. Blocking of estrone synthesis by the aromatase inhibitor letrozole is counteracted by an increase in ER-? and ER-?. In addition, CYP1A1, an enzyme involved in catabolic estrogen metabolism, is upregulated. This suggests that articular chondrocytes use ERs functionally. The role of endogenous synthesized estrogens in articular cartilage health remains to be elucidated.
EVALuna2:4411

Automated Digital Image Optimisation in Intraoperative 2D and 3D Imaging Using a Mobile C-Arm With Flat-Panel Detector - Groh, Johannes; Perl, Markus; Bräuer, Lars; Stadthalter, Holger (International Journal of Medical Robotics and Computer Assisted Surgery, 2025)
Background: Assistance tools for intraoperative 2D and 3D imaging to decrease acquisition effort and to improve assessment of 3D image data were evaluated. Methods: Two automated optimisation procedures were evaluated in a cadaver (Cios Spin, Siemens, Germany): The ScrewScout function for assisted pedicle screw assessment. Then, an algorithm for metal artefact reduction (MAR). Additionally, a tool for simplified setting of image contrast and brightness was evaluated regarding the result and elapsed time. Results: The time required without automated assistance was 83s [70–105]. With the computer assistance, this time was significantly lower at 22s [15–32] (p = 0.003). MAR resulted in an improvement in image impression. This improvement became smaller with increasing clinical experience. The time needed for setting of image acquisition parameters was significantly (p = 0.05) lowered from 140s [24–389] to 61s [14–166] using the assistance tool. Conclusions: Automated assistance tools for image optimisation can provide practical support in the intraoperative setting.
CRIS-Team Scopus Importer:2025-03-14
Keywords: automated image analysis; intraoperative imaging; MAR; metal artifact reduction; ScrewScout; SpotAdapt

Characterization of the mucocutaneous junction of the human eyelid margin and meibomian glands with different biomarkers - Tektas, Ozan Yüksel; Yadav, Ajay; Garreis, Fabian; Schlötzer-Schrehardt, Ursula; Schicht, Martin; Hampel, Ulrike; Bräuer, Lars; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2012)
To investigate the morphology of the human eyelid margin and the presence of different cytokeratins, mucins and stem cell markers within the skin epithelium, mucocutaneous junction (MCJ) and palpebral conjunctiva.Eyelids of body donors were investigated histologically and ultrastructurally as well as by immunohistochemical methods using antibodies to cytokeratins 1, 4, 7, 8, 10, 13, 14, 15, and 19; mucins MUC1, MUC4, and MUC5AC and potential stem cell markers K15, BCRP/ABCG2, integrin ?1, and N-cadherin.The expression pattern of cytokeratins, mucins and stem cell markers varied across the different epithelia of the human eyelid. Within the MCJ, CK7, 15 and 19 were absent, whereas the epithelium reacted positive to antibodies to CK1, 4, 8, 10, 13 and 14. Reactivity was also observed for MUC1 and MUC4, but not for MUC5AC. No reactivity was determined for K15, BCRP/ABCG2 and integrin ?1 in the area of the MCJ epithelium but a strong reactivity was present for N-cadherin.The present immunohistochemical findings lead to a better characterization of the MCJ. Additionally, the knowledge of distribution of biomarkers like cytokeratins, mucins and stem cells can be useful in the investigation of MCJ disturbances which occur in several disorders of the meibomian glands and the lid epithelium in the course of dry eye syndrome and especially meibomian gland dysfunction.
EVALuna2:4382

Cluster analyses of contemporary embalming protocols in central European anatomy institutions: A collaborative effort to minimize chemical exposure - Mohebimoushaei, Sara; Antipova, Veronica; Biedermann, Uta; Brand-Saberi, Beate; Bräuer, Lars; Caspers, Svenja; Doll, Sara; Engelhardt, Maren; Filler, Timm J.; Gericke, Martin; Gümüsalan, Yakup; Gundlach, Stefanie; et al. (Annals of Anatomy-Anatomischer Anzeiger, 2025)
Background: Anatomical embalming forms a mainstay in the provision of teaching materials based on human post-mortem tissues. As a consequence of regulations worldwide to minimize the use of formaldehyde due to its harmful nature, effective measures must be taken to minimize its application in the anatomy laboratory. This study aimed to identify commonalities among embalming protocols used in Austrian, German and Swiss anatomies to reduce formaldehyde usage and provide a foundation for joint accreditation. Methods: Survey data on all procedures, technologies and chemicals related to embalming were collected from 28 participating institutions and analyzed using an automated clustering approach. Special attention was given to chemicals, explosion-proof facilities, and air ventilation technology. After conducting principal component analyses, the data was evaluated using an unsupervised K-means learning algorithm. Results: Six distinct clusters of common chemical usage were identified, namely (1) Thiel embalming with explosion-proof facilities, (2) potassium- and sodium salt-based embalming with downdraft ventilation, (3) ethanol/glycerin/glutaraldehyde/sodium alkyl ether sulphate-based embalming, (4) ethanol-based embalming, (5) formaldehyde-based embalming, and (6) ethanol/phenoxyethanol/alkyl (C12–16) dimethylbenzyl ammoniumchloride-based embalming. All clusters included the use of formaldehyde to varying extent. These clusters demonstrated high stability for fixation, combined fixation and conservation, as well as the incorporation of explosion-proof facilities and air ventilation technology. Moreover, a number of institutions used more than one similar protocol, so-called ‘Superclusters’, with Clusters (4) and (1) or Clusters (5) and (1) combined being the most common observation. Conclusion: These findings provide a basis for optimizing, streamlining and sharing embalming protocols among central European anatomy institutions.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cluster analysis; Conservation; Elbow method; Embalming; Fixation; Formaldehyde

Coactivation of the Laryngeal Muscles in Pigs Without External Neural Control Indicates Existence of an Intrinsic Neuronal Network - Tracicaru, Rareş Vasile; Bräuer, Lars; Döllinger, Michael; Tamba, Bogdan Ionel; Szilagyi, Andrei; Catalin, Caratasu Cezar; Hînganu, Delia; Paulsen, Friedrich; Hînganu, Marius Valeriu (Journal of Voice, 2024)
Electrophysiological studies of the larynx expose the mechanisms by which voice production is controlled. Previous studies have revealed certain phenomena during laryngeal oscillations that suggest a complex control mechanism. Starting from the principle of agonist-antagonist muscular pairing, the aim of this study was to gain a deeper insight into the function of the cricothyroid (CT) and thyroarytenoid (TA) muscles, both central to voice production. Electromyographic recordings were used to determine the response of the two muscles to different stimulation situations in an ex vivo animal model of the denervated larynx of pigs (n = 26). Using a set of different experiments, it was shown that when one muscle (CT or TA muscle) was electrically stimulated, a response was observed in the other muscle, which in the otherwise-denervated larynx, was caused only by the applied stimulation and exhibited the characteristics of compound action potentials. This response was reproducible in all larynxes examined and was present bidirectionally. No response was registered in the absence of stimulation. The results show the existence of coactivation of the CT and TA muscles in the absence of external innervation hinting at the presence of a localized neuronal network of the larynx that has not been described previously. Further morphological investigation is needed to determine the presence of this internal laryngeal neuronal network.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Animal model; Electromyography; Larynx; Muscles; Neural network; Reflex

Complex mechanical behavior of human articular cartilage and hydrogels for cartilage repair - Weizel, A.; Distler, Thomas; Schneidereit, Dominik; Friedrich, Oliver; Bräuer, Lars; Paulsen, Friedrich; Detsch, Rainer; Boccaccini, Aldo R.; Budday, Silvia; Seitz, H. (Acta Biomaterialia, 2020)
The mechanical behavior of cartilage tissue plays a crucial role in physiological mechanotransduction processes of chondrocytes and pathological changes like osteoarthritis. Therefore, intensive research activities focus on the identification of implant substitute materials that mechanically mimic the cartilage extracellular matrix. This, however, requires a thorough understanding of the complex mechanical behavior of both native cartilage and potential substitute materials to treat cartilage lesions. Here, we perform complex multi-modal mechanical analyses of human articular cartilage and two surrogate materials, commercially available ChondroFillerliquid, and oxidized alginate-gelatin (ADA-GEL) hydrogels. We show that all materials exhibit nonlinearity and compression-tension asymmetry. However, while hyaline cartilage yields higher stresses in tension than in compression, ChondroFillerliquid and ADA-GEL exhibit the opposite trend. These characteristics can be attributed to the materials’ underlying microstructure: Both cartilage and ChondroFillerliquid contain fibrillar components, but the latter constitutes a bi-phasic structure, where the 60% nonfibrillar hydrogel proportion dominates the mechanical response. Of all materials, ChondroFillerliquid shows the most pronounced viscous effects. The present study provides important insights into the microstructure-property relationship of cartilage substitute materials, with vital implications for mechanically-driven material design in cartilage engineering. In addition, we provide a data set to create mechanical simulation models in the future.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Human articular cartilage; Hydrogels; Mechanical testing; Microstructure; Tissue engineering

Concise report: a minimal-invasive method to retrieve and identify entheseal tissue from psoriatic arthritis patients - Pachowsky, Milena; Raimondo, Maria Gabriella; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (Annals of the Rheumatic Diseases, 2022)
Objectives To establish a minimally invasive biopsy technique for the analysis of entheseal tissue in patients with psoriatic arthritis (PsA). Methods Human cadavers were used for establishing the technique to retrieve tissue from the lateral humeral epicondyle enthesis (cadaveric biopsies). After biopsy, the entire enthesis was surgically resected (cadaveric resections). Biopsies and resections were assessed by label-free second harmonic generation (SHG) microscopy. The same technique was then applied in patients with PsA with definition of entheseal tissue by SHG, staining of CD45+immune cells and RNA extraction. Results Entheseal biopsies from five cadavers allowed the retrieval of entheseal tissue as validated by the analysis of resection material. Microscopy of biopsy and resection sections allowed differentiation of entheseal, tendon and muscle tissue by SHG and definition of specific intensity thresholds for entheseal tissue. In subsequent entheseal biopsies of 10 PsA patients: the fraction of entheseal tissue was high (65%) and comparable to cadaveric biopsies (68%) as assessed by SHG microscopy. Furthermore, PsA biopsies showed immune cell infiltration and sufficient retrieval of RNA for further molecular analysis. Conclusion Entheseal biopsy of the lateral epicondyle is feasible in patients with PsA allowing reliable retrieval of entheseal tissue and its identification by SHG microscopy.
CRIS-Team WoS Importer:2022-05-13

Corrigendum to “Internal vascular anatomy of the human lacrimal gland: A protocol based on cadaver dissection and three-dimensional micro-computed tomography” [Ann. Anat. 252 (2024) 152207] (Annals of Anatomy (2024) 252, (S0940960223001620), (10.1016/j.aanat.2023.152207)) - Singh, Swati; Chopra, Prakshi; Necker, Fabian; Scholz, Michael; Liphardt, Anna-Maria; Schuster, Louis; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2024)
The authors regret in the article by Singh et al. in volume 252;152207, February 2024, of Annals of Anatomy, the following change should be made in the acknowledgement section: 1. The present work was performed in (partial) fulfillment of the requirements for obtaining the degree of Dr. med (SS).The additional information provided does not influence the conclusions of the study. The authors would like to apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2024-05-31

Corrigendum to "New insights into lacrimal gland anatomy using 7T MRI and electron microscopy: Relevance for lacrimal gland targeted therapies and bioengineering" [Ocul. Surf. 30 (October 2023) 204-212]. - Singh, Swati; Winter, Zoltan; Necker, Fabian; Bäuerle, Tobias; Scholz, Michael; Bräuer, Lars; Paulsen, Friedrich (Ocular Surface, 2024)
EVALuna2:568452

Corrigendum to "Recombinant expression of surfactant protein H (SFTA3) in Escherichia coli" [Ann. Anat. 208C (2016) 129-134] - Schröder, Henrik; Sollfrank, L.; Paulsen, Friedrich; Bräuer, Lars; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2017)
EVALuna2:34488

Detection of intrinsic cholinergic system in the human lacrimal drainage system: evidence and potential implications - Mohammad, Javed Ali; Glöckner, Mareile; Schicht, Martin; Bräuer, Lars; Paulsen, Friedrich (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: To investigate the presence and distribution of epithelial and non-epithelial cholinergic system and cholinergic brush cells in the human lacrimal drainage system. METHODS: The study was performed on fresh frozen human cadaveric samples of the lacrimal drainage system. Immunohistochemistry was performed for assessing the presence and distribution of cholinergic brush cell proteins-villin, acetylcholine synthesizing enzyme, choline acetyltransferase (ChAT); vesicular acetylcholine transporter (VAChT); components of canonical taste transduction signaling cascade, phospholipase C β2 (PLCβ2), and transient receptor potential cation channel, subfamily M, and member 5 (TRPM5). In addition, immunoreactivity to carbonic anhydrase 4 (CA4) was assessed. The immunoreactivity was scored as positive or negative and the distribution patterns in the canaliculi, lacrimal sac, and nasolacrimal duct were investigated. In addition, ultrastructural analysis was performed to ascertain the presence of brush cells by means of scanning electron microscopy (SEM). RESULTS: Villin revealed immunoreactivity in the superficial epithelial cells of lacrimal sac and nasolacrimal ducts. Positive immunoreactivity was also found for ChAT, VAChT, TRPM5, and PLCβ2. ChAT expression was limited to the superficial epithelial layers of the lacrimal sac epithelium. TRPM5 and PLCβ2 were expressed on the cell membranes, cytoplasm, and basolateral surfaces of the lacrimal sac epithelium and also showed strong expression in the submucosal glandular acinar cells. VAChT showed strong expression in the canaliculus and lacrimal sac and was expressed on the surface of the superficial epithelial cells and the submucosal glandular acinar cells and lining of the blood vessels. There was a uniformly negative immunoreactivity for CA4. SEM revealed single epithelial cells with dense tuft of rigid apical microvilli in the lacrimal sac and nasolacrimal ducts. CONCLUSIONS: This study provides a proof of principle for the presence of an intrinsic epithelial cholinergic mechanism in the lacrimal drainage system.
EVALuna2:35303

Detection of surfactant proteins A, B, C, and D in human nasal mucosa and their regulation in chronic rhinosinusitis with polyps - Schicht, Martin; Knipping, Stephan; Hirt, Roman; Beileke, Stephanie; Sel, Saadettin; Paulsen, Friedrich; Bräuer, Lars (American Journal of Rhinology & Allergy, 2013)
Backround: The nasal mucosa is characterized by a multirow high prismatic ciliated epithelium representing the first barrier of the immune defense system against microbial and other environmental pathogenic influences. A number of nonspecific defense mechanisms, including the presence of lactoferrin, peroxidases, proteases, interferons, and lysozymes in nasal secretions, act to counter inflammatory processes. The surfactant proteins (SPs) known from the lungs are important components of the innate immune system. They also influence the rheology of fluids and reduce the surface tension of gas-fluid interphases. The objective of this study was to investigate the protein expression of all four SPs. A specific aim was detection and characterization of SP-C, which had previously not been confirmed in human nasal mucosa. Methods: The expression of mRNA for SP-A, -B, -C and -D was investigated using reverse transcriptase polymerase chain reaction on samples of both healthy nasal mucosa and nasal mucosa altered by inflammatory processes (allergic rhinitis and chronic rhinosinusitis). The distribution of all four proteins was determined with monoclonal antibodies using Western blot analysis as well as immunohistochemical methods. Results: The results show that all four SPs, including SP-C not detected before this, are nasal mucosa components. A shift was also observed in the expression behavior of the SP-A, -B, and -D in nasal mucosa with inflammatory changes. Conclusion: Based on these results, SPs appear to have an important function in immunologic and rheological process of the nasal mucosa and support the prospective therapeutic use of liposomal nasal sprays. Copyright © 2013, OceanSide Publications, Inc., U.S.A.
CRIS-Team Scopus Importer:2022-08-05

Efficacy of aflibercept (EYLEA®) on inhibition of human VEGF in vitro - Schicht, Martin; Hesse, Karen; Schröder, Henrik; Naschberger, Elisabeth; Lamprecht, W.; Garreis, Fabian; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2017)
Pathological formation of blood vessels plays a key role in the growth and metastasis of tumors and also in several serious ophthalmological diseases such as wet age-related macular degeneration (AMD) or diabetic retinopathy. In AMD treatment, aflibercept (tradename EYLEA®) is used to deactivate the underlying pathological neovascularisation. Aflibercept is a recombinant fusion protein which binds to vascular endothelial growth factor (VEGF) receptors, thereby inhibiting VEGF pathway activation. VEGF is one of the most important angiogenesis factors.This analysis investigates lasting efficacy of aflibercept in vitro for later application as therapeutic agent against macular degeneration (AMD).VEGF-ELISA assays were performed to investigate binding affinities at different aflibercept concentrations. The impact of VEGF on the proliferation of human umbilical vein endothelial cells (HUVEC) was investigated using proliferation assays. Moreover, time-dependent kinetic studies were performed to analyze different aflibercept storage durations with regard to its inhibitory capabilities on human VEGF.Our results reveal that aflibercept significantly lowers the amount of unbound VEGF as well as the proliferation rate of HUVEC. Moreover, in contrast to specifications given by the manufacturer, aflibercept retains its full inhibitory effect up to at least 120h after transference from the original vial into the injection syringe.
EVALuna2:15305
Keywords: Aflibercept; VEGF; VEGF-trap; EYLEA®; HUVEC

Entheseal Biopsy Approach: An Ultrasound-guided Method for Retrieval of Entheseal Tissue from Psoriatic Arthritis Patients - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Evaluation of surfactant proteins A, B, C, and D in articular cartilage, synovial membrane and synovial fluid of healthy as well as patients with osteoarthritis and rheumatoid arthritis - Hartjen, Nadine; Bräuer, Lars; Reiss, Beate; Claassen, Horst; Beileke, Stephanie; Garreis, Fabian; Hoogeboom, Sebastian; Tsokos, Michael; Etzold, Saskia; Mueller-Hilke, Brigitte; Gelse, Kolja; Mueller, Thomas; et al. (PLoS ONE, 2018)
OBJECTIVE: Surfactant Proteins (SPs) are well known from lung and form, along with phospholipids, a surface-active-layer at the liquid-air-interface of the alveolar lining. They play a major protective role by lowering surface tension, activating innate and adaptive immune defense at the lung mucosal interface, especially during infection. We analyzed the regulation of SPs in human and mouse articular chondrocytes, synoviocytes, and synovial fluid under healthy and inflammatory conditions, as well as in tissues of patients suffering from osteoarthritis and rheumatoid arthritis. METHODS: Immunohistochemistry, RT-PCR, qRT-PCR, ELISA, Western blotting were performed in cell cultures and tissue samples to determine localization, regulation, and concentration of SPs. RESULTS: All four SPs, were expressed by healthy human and mouse articular chondrocytes and synoviocytes and were also present in synovial fluid. Treatment with inflammatory mediators like IL-1β and TNF-α led to short-term upregulation of individual SPs in vitro. In tissues from patients with osteoarthritis and rheumatoid arthritis, protein levels of all four SPs increased significantly compared to the controls used. CONCLUSION: These results show the distribution and amount of SPs in tissues of articular joints. They are produced by chondrocytes and synoviocytes and occur in measurable amounts in synovial fluid. All four SPs seem to be differently regulated under pathologic conditions. Their physiological functions in lowering surface tension and immune defense need further elucidation and make them potential candidates for therapeutic intervention.
EVALuna2:35305

Examining the role of the surfactant family member SFTA3 in interneuron specification - Chen, Christopher Y.; Anderson, Nickesha C.; Becker, Sandy; Schicht, Martin; Stoddard, Christopher; Bräuer, Lars; Paulsen, Friedrich; Grabel, Laura (PLoS ONE, 2018)
The transcription factor NKX2.1, expressed at high levels in the medial ganglionic eminence (MGE), is a master regulator of cortical interneuron progenitor development. To identify gene candidates with expression profiles similar to NKX2.1, previous transcriptome analysis of human embryonic stem cell (hESC)-derived MGE-like progenitors revealed SFTA3 as the strongest candidate. Quantitative real-time PCR analysis of hESC-derived NKX2.1-positive progenitors and transcriptome data available from the Allen Institute for Brain Science revealed comparable expression patterns for NKX2.1 and SFTA3 during interneuron differentiation in vitro and demonstrated high SFTA3 expression in the human MGE. Although SFTA3 has been well studied in the lung, the possible role of this surfactant protein in the MGE during embryonic development remains unexamined. To determine if SFTA3 plays a role in MGE specification, SFTA3-/- and NKX2.1 -/- hESC lines were generated using custom designed CRISPRs. We show that NKX2.1 KOs have a significantly diminished capacity to differentiate into MGE interneuron subtypes. SFTA3 KOs also demonstrated a somewhat reduced ability to differentiate down the MGE-like lineage, although not as severe relative to NKX2.1 deficiency. These results suggest NKX2.1 and SFTA3 are co-regulated genes, and that deletion of SFTA3 does not lead to a major change in the specification of MGE derivatives.
EVALuna2:35300

Expression analysis of ADAM17 during mouse eye development - Sel, Saadettin; Kalinski, Thomas; Enssen, Isabelle; Kaiser, Maja; Nass, Norbert; Trau, Stefanie; Wollensak, Gregor; Bräuer, Lars; Jaeger, Kristin; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2012)
ADAM17 (a disintegrin and metallopeptidase domain 17) is crucial for eye morphogenesis. In this study we analysed the expression pattern of ADAM17 during mouse eye development. ADAM17 expression in adult retina was examined using the reverse transcription-polymerase chain reaction (RT-PCR) and verification of the RT-PCR products by DNA sequencing. Immunohistochemistry was performed to evaluate the ADAM17 expression pattern in mouse eyes at developmental stages of embryonic day (E) 12, E14, E16, E18, postnatal day (P) 0, P1, P4, P7, P14, P 30 and P175 (adult). We detected ADAM17 mRNA in adult retina tissue. ADAM17 protein was expressed in non-pigmented ciliary epithelial cells and in retinal vessels from P7 onwards during eye development. In corneal epithelial cells and endothelium, ADAM17 protein was present from P14 onwards. Although, mice in which the functional ADAM17 gene is significantly reduced develop multiple eye malformations, the expression of ADAM17 is not ubiquitous over the entire eye. Its expression pattern during development suggests that not only TNF-alpha but additional membrane-anchored substrates of ADAM17 play an important role in eye formation.
EVALuna2:4384

Expression and Localization of Lung Surfactant Proteins in Human Testis - Beileke, Stephanie; Claassen, Horst; Wagner, Walter; Matthies, Cord; Ruf, Christian; Hartmann, Arndt; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (PLoS ONE, 2015)
Surfactant proteins (SPs) have been described in various tissues and fluids including tissues of the nasolacrimal apparatus, airways and digestive tract. Human testis have a glandular function as a part of the reproductive and the endocrine system, but no data are available on SPs in human testis and prostate under healthy and pathologic conditions.The aim of the study was the detection and characterization of the surfactant proteins A, B, C and D (SP-A, SP-B, SP-C, SP-D) in human testis. Additionally tissue samples affected by testicular cancer were investigated.Surfactant proteins A, B, C and D were detected using RT-PCR in healthy testis. By means of Western blot analysis, these SPs were detected at the protein level in normal testis, seminoma and seminal fluid, but not in spermatozoa. Expression of SPs was weaker in seminoma compared to normal testicular tissue. SPs were localized in combination with vimentin immunohistochemically in cells of Sertoli and Leydig.Surfactant proteins seem to be inherent part of the human testis. By means of physicochemical properties the proteins appear to play a role during immunological and rheological process of the testicular tissue. The presence of SP-B and SP-C in cells of Sertoli correlates with their function of fluid secretion and may support transportation of spermatozoa. In seminoma the expression of all SP's was generally weaker compared to normal germ cells. This could lead to a reduction of immunomodulatory and rheology processes in the germ cell tumor.
EVALuna2:4444

Expression of recombinant surfactant protein SFTA3 in the human kidney cell line HEK 293T - Schröder, Henrik; Fischer, Ronny; Sollfrank, L.; Paulsen, Friedrich; Bräuer, Lars; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2017)
Pulmonary surfactant is broadly known to keep the lung dry, clean and open by lowering the surface tension of the fluid-film that lines the alveoli. The surfactant's protein component, the so called surfactant proteins (SPs), make up a multifunctional protein family. In addition to the four "classical" surfactant proteins (SP-A, SP-B, SP-C and SP-D), which possess immunologic as well as surfactant regulatory properties, two novel putative surfactant proteins (SFTA2 and SFTA3) have recently been described. Neither of them shows sequential nor structural similarity with the already known surfactant proteins. However, bioinformatic analyses as well as first molecular-biological studies reveal properties that have already been described for known surfactant proteins. In our present work we introduce a technique to synthesize, purify and stabilize recombinant SFTA3 derived from the human embryonic kidney cell line HEK 293T. This will provide investigators with a valuable source of further examination and characterization of this fascinating novel member of the surfactant protein family.
EVALuna2:34489

Expression of Surfactant Proteins in the Human Canaliculus: Evidence and Potential Insights Into the Tear Flow Dynamics - Mohammad, Javed Ali; Kumar, Nadimpalli Siva; Bräuer, Lars; Paulsen, Friedrich; Schicht, Martin (Ophthalmic Plastic and Reconstructive Surgery, 2018)
PURPOSE: To investigate the presence and distribution patterns of 6 surfactant proteins (SPs) in the human lacrimal canaliculus. METHODS: The study was performed on fresh frozen cadaveric samples of canaliculi. Immunohistochemical labeling was performed for assessing the presence and distribution of SP: SP-A, SP-B, SP-C, SP-D, SP-G/SFTA2, and SP-H/SFTA3. Immunofluorescence double staining was performed using the respective fluorescein-conjugated antibodies and the results were scored as positive or negative and the distribution pattern within the canalicular system was assessed. Western blot analysis was performed on the protein content which was resolved by reducing 15% sodium dodecyl sulfate-polyacrylamide electrophoresis and bands were studied following staining with primary and secondary antibodies. Human lung tissues were used as controls. RESULTS: Fluorescence double staining with 4,6-diamidino 2-pheynlindole and SPs showed strong immunostaining for SP-A, SP-B, SP-C, SP-D, and SP-H/SFTA3. The positive immunofluorescence was noticed across all the layers of the epithelium but not the subepithelial structures. The expression was noted on the surfaces and superficial cytoplasm of the superficial and deep epithelial cells. There was no expression of SP-G/SFTA2 across the canalicular system. Western blot analysis of the proteins confirmed and concurred with the immunofluorescence findings. CONCLUSIONS: This study provides a proof of principle for the presence of SPs known from lungs in the canalicular system and hypothesizes their possible functions and also their potential role in the tear flow dynamics between the ocular surface and the lacrimal drainage system.
EVALuna2:35301

Flexor tendon repair with a polytetrafluoroethylene (PTFE) suture material - Polykandriotis, Elias; Besrour, Foued; Arkudas, Andreas; Ruppe, Florian; Zetzmann, Katharina; Bräuer, Lars; Horch, Raymund E. (Archives of Orthopaedic and Trauma Surgery, 2019)
BackgroundThere is a consensus that after a flexor tendon repair an aggressive rehabilitation protocol with early active motion can improve functional outcome, provided that the combination of material and suturing technique can meet the higher biomechanic demands. Bearing this in mind we evaluated a polytetrafluoroethylene (PTFE) suture (SERAMON((R)), Serag-Wiessner) as a possible material for flexor tendon repair.Materials and methods40 flexor tendons were harvested from fresh cadaveric upper extremities. 3-0 and 5-0 strands were used both in the polypropylene (PPL) as well as in the PTFE group. In the first phase of the study, we evaluated knotting properties and mechanical characteristics of the suture materials themselves. In the second phase, a 2-strand Kirchmayr-Kessler suture technique was applied for a core suture of a flexor tendon (n=16). In the third phase, we performed a tendon repair including an epitendinous running suture with 5-0 PPL or 5-0 PTFE material (n=22). One way ANOVA tests were performed.ResultsThe linear loading strength of single strand knotted PPL 3-0 was 19.870.59N. The linear loading strength of knotted PTFE 3-0 was 32.47 +/- 1.67N. For PPL 3-0 maximum linear strength was achieved with five knots, for PTFE 3-0 with eight knots. When a Kirchmayr-Kessler core-only repair was performed, then in the PPL group the loading strength of the repaired tendon was 30.74 +/- 9.77N. In the PTFE group the loading strength was 23.74 +/- 5.6N (p=0.10). However, all repairs in the PTFE group failed due to cheese wiring. When a Kirchmayr-Kessler core and epitendinous repair technique was used, then in the PPL group the loading strength of the repaired tendon was 49.90 +/- 16.05N. In the PTFE group the loading strength was 73.41 +/- 19.81N (p=0.006).Conclusion p id=Par4 PTFE demonstrates superior strength properties in comparison to PPL for flexor tendon repairs. However, standard 2 strand techniques have proved inadequate to bear the higher biomechanic demands.
CRIS-Team WoS Importer:2019-03-08

Functional Protective Effects of Long-Term Memantine Treatment in the DBA/2J Mouse. - Atorf, Jenny; Scholz, Michael; Garreis, Fabian; Lehmann, Julia; Bräuer, Lars; Kremers, Jan (Documenta Ophthalmologica, 2013)
Purpose: To analyse the effects of long-term memantine treatment on the retinal physiology and morphology of DBA/2J mice. Methods: DBA/2J (D2J) mice received i.p. injections of the NMDA receptor antagonist memantine, which protects neurons from abnormally elevated glutamate levels, twice a day over a period of 7 months. At the age of 2, 6 and 10 months, the intraocular pressure (IOP) and electroretinograms (ERGs) were measured in all treated D2J mice, in untreated D2J controls and in C57Bl/6 (B6) wild-type mice. After the last measurement at the age of 10 months, the mice were killed and the retinae and the optic nerves were analysed morphologically. Results: The IOP increased with age in both D2J and B6 mice with a larger increase in the D2J strain. IOPs were not influenced by memantine treatment. The response amplitude of the scotopic flash ERG decreased with age in the D2J strain. This amplitude decrease, particularly that of the b-wave, was smaller in treated D2J mice. The retinae of treated D2J mice exhibited less peripheral degeneration of cone photoreceptors, and optic nerve neuropathy was less frequent. Conlcusions: Application of the NMDA receptor antagonist memantine diminished retinal neurodegeneration in the D2J mice and had a protective effect on the b-wave amplitude of the scotopic flash ERG. This protection may occur secondarily as memantine primarily acts on retinal ganglion cells. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.med.AI.LAIPDL.functi
Keywords: DBA/2J mouse; Electroretinography; Memantine; Neurodegeneration

Gibt es eine neue Kopfspeicheldrüse? – Eher nicht! - Guntinas-Lichius, Orlando; Ihrler, Stephan; Freesmeyer, Martin; Guehne, Falk; Kluge, Regine; Bräuer, Lars; Iro, Heinrich; Paulsen, Friedrich; Dietz, Andreas; Bechmann, Ingo (Laryngo-Rhino-Otologie, 2020)
In October 2020, the lay press, but also some medical journals and websites reported the putative discovery of a new salivary gland in the nasopharynx based on prostate-specific membrane antigen positron emission tomography computed tomography (PSMA-PET/CT) examinations. As an interdisciplinary group from the fields of anatomy, pathology, nuclear medicine and otorhinolaryngology, we come to the view that an accumulation of minor salivary glands has been described here. Minor salivary glands in the nasopharynx and in the peritubar region have been described at least since 1866. The current description in PSMA-PET/CT does not justify the definition of a new, independent salivary gland. The PSMA-PET/CT could, however, be suitable to better protect salivary glands in the nasopharynx when planning radiation therapy. This should be evaluated in clinical trials.
CRIS-Team Scopus Importer:2020-12-04

Historical Profiling of Dry Eye Patients - Potential Trigger Factors and Comorbidities - Posa, Andreas; Sel, Saadettin; Dietz, Richard; Sander, Ralph; Paulsen, Friedrich; Bräuer, Lars; Hammer, Christian (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose Dry eye syndrome (DES) is one of the most common diseases of the ocular surface. Affected persons suffer from different subjective complaints, with sometimes severe impairment in the quality of life. The aetiology and pathogenesis are multifactorial, multifaceted, and not yet fully understood. The present study is intended to provide deeper insights into possible triggering factors and correlating comorbidities.Materials and Methods In German ophthalmological practices, 306 persons (174 women, 132 men, age: 18 - 87 years) were interviewed by questionnaire on concomitant diseases and possible further triggering factors. DES was diagnosed by an ophthalmologist in 170 cases. The statistical comparative analysis between persons with and without DES was carried out using the chi-squared test (SPSS statistical software).Results DES occurred with significantly (p < 0.05) increased frequency in women over 40 years of age, as well as in persons exposed to screen work, air conditioning, persons with chronic ocular inflammation, myomas (hysterectomy), dry skin, arterial hypertonicity in need of medication, cardiac arrhythmias, fatty liver, gastric ulcer, appendicitis, cholecystectomy, depression, hyperlipidaemia, hyperuricaemia, osteoporosis, and nephrolithiasis.Conclusion Some of the known comorbidities and DES risk factors, e.g., computer work or depression, were confirmed. In contrast, the higher prevalence of hyperlipidaemia, hyperuricaemia, osteoporosis, nephrolithiasis, and fibroids among DES patients has not previously been reported. Additional studies should be performed on causal connections between DES and specific comorbidities.
CRIS-Team WoS Importer:2023-05-05

Hyperelastic parameter identification of human articular cartilage and substitute materials - Weizel, A.; Distler, Thomas; Detsch, Rainer; Boccaccini, Aldo R.; Paulsen, Friedrich; Seitz, H.; Budday, Silvia; Bräuer, Lars (Journal of the Mechanical Behavior of Biomedical Materials, 2022)
Numerical simulations are a valuable tool in the field of tissue engineering for cartilage repair and can help to understand which mechanical properties affect the behavior of chondrocytes and contribute to the success or failure of surrogate materials as implants. However, special attention needs to be paid when identifying corresponding material parameters in order to provide reliable numerical predictions of the material's response. In this study, we identify hyperelastic material parameters for numerical simulations in COMSOL Multiphysics (R) v. 5.6 for human articular cartilage and two surrogate materials, commercially available ChondroFiller(liquid), and oxidized alginate-gelatin (ADA-GEL) hydrogels. We consider several hyperelastic isotropic material models and provide separate parameter sets for the unconditioned and the conditioned material response, respectively, based on previously generated experimental data including both compression and tension experiments. We compare a direct parameter identification approach assuming homogeneous deformation throughout the specimen and an inverse approach, where the experiments are simulated using a finite element model with realistic boundary conditions in COMSOL Multiphysics (R) v. 5.6. We demonstrate that it is important to consider both compression and tension data simultaneously and to use the inverse approach to obtain reliable parameters. The one-term Ogden model best represents the unconditioned response of cartilage, while the conditioned response of cartilage and ADA-GEL is equally well represented by the two-term Ogden and five-term Mooney-Rivlin models. The five-term Mooney-Rivlin model is also most suitable to model the unconditioned response of ADA-GEL. For ChondroFiller(liquid), we suggest using the five-term Mooney-Rivlin or two-term Ogden model for the unconditioned and the two-term Ogden model for the conditioned material response. These results will help to choose appropriate material models and parameters for simulations of whole joints or to advance mechanical-stimulation assisted cartilage tissue engineering in the future.
CRIS-Team WoS Importer:2022-07-01
Keywords: Parameter identification; Finite hyperelasticity; Human articular cartilage; Hydrogels; Tissue engineering

Identifying composition-mechanics relations in human brain tissue based on neural-network-enhanced inverse parameter identification - Hinrichsen, Jan; Feiler, Lea; Reiter, Nina; Bräuer, Lars; Schicht, Martin; Paulsen, Friedrich; Budday, Silvia (Mathematics and Mechanics of Solids, 2024)
The mechanical properties of human brain tissue remain far from being fully understood. One aspect that has gained more attention recently is their regional dependency, as the brain’s microstructure varies significantly from one region to another. Understanding the correlation between tissue components and the mechanical behavior is an important step toward better understanding how human brain tissue properties change in space and time and to develop highly spatially resolved constitutive models for large-scale brain simulations. Here, we analyze the correlation between human brain tissue components quantified through enzyme-linked immunosorbent assays (ELISA) and material parameters obtained through an inverse parameter identification scheme based on a hyperelastic Ogden model and multimodal mechanical testing data for eight regions of the brain. We use neural networks as a metamodel to save computational costs. The networks are trained on finite element simulation outputs and are able to replace the simulations in the initial optimization step. We identified strong dependencies between mechanical properties and Iba1 associated with microglia cells, collagen VI, GFAP associated with astrocytes, and collagen IV. These results advance our understanding of microstructure-mechanics relations in human brain tissue and will contribute to the development of highly spatially resolved microstructure-informed constitutive models.<br

Internal vascular anatomy of the human lacrimal gland: A protocol based on cadaver dissection and three-dimensional micro-computed tomography - Singh, Swati; Chopra, Prakshi; Necker, Fabian; Scholz, Michael; Liphardt, Anna-Maria; Schuster, Louis; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Purpose: To evaluate the feasibility of studying the vascular supply of the orbital and palpebral lobes of the human lacrimal gland using micro-computed tomography (micro-CT) and microscopic dissection. Methods: The lacrimal gland artery of a fresh parasagittalized cadaver head (male, aged 76 years) was infused with a lead oxide-latex mixture near the occipital pole of the gland. The entire lacrimal gland was imaged using micro-CT and 3D cinematic rendering (CR) and then dissected under a surgical microscope. Results: Micro-CT and CR images showed well-demarcated internal vascular branches of the lacrimal artery and their distribution within the orbital and palpebral lobes. The entire course of the artery and its branches could be visualized by CR and microscopic dissection, with the former showing better spatial orientation and finer branching. The main artery runs along the free edge of the aponeurosis of the levator palpebrae superior muscle and lies in the isthmus portion of the gland (between the orbital and palpebral lobes). The branches of the main lacrimal artery include one branch to the orbital adipose tissue just before entering the gland, two branches to the orbital lobe (medial and lateral), and two branches to the palpebral lobe (medial and lateral). The main artery terminates as palpebral and orbital lobe branches in the lateral half of the lacrimal gland. Conclusion: Latex and contrast-enhanced micro-CT is very well suited to visualize the vascular anatomy of the lacrimal artery within the gland. A large number of lacrimal gland examinations using the method presented here are required to demonstrate and understand the variability of the vascular anatomy of the human lacrimal gland.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Anatomy; CT; Dry eye disease; Lacrimal artery; Lacrimal gland

Inverse identification of region-specific hyperelastic material parameters for human brain tissue - Hinrichsen, Jan; Reiter, Nina; Bräuer, Lars; Paulsen, Friedrich; Käßmair, Stefan; Budday, Silvia (Biomechanics and Modeling in Mechanobiology, 2023)
The identification of material parameters accurately describing the region-dependent mechanical behavior of human brain tissue is crucial for computational models used to assist, e.g., the development of safety equipment like helmets or the planning and execution of brain surgery. While the division of the human brain into different anatomical regions is well established, knowledge about regions with distinct mechanical properties remains limited. Here, we establish an inverse parameter identification scheme using a hyperelastic Ogden model and experimental data from multi-modal testing of tissue from 19 anatomical human brain regions to identify mechanically distinct regions and provide the corresponding material parameters. We assign the 19 anatomical regions to nine governing regions based on similar parameters and microstructures. Statistical analyses confirm differences between the regions and indicate that at least the corpus callosum and the corona radiata should be assigned different material parameters in computational models of the human brain. We provide a total of four parameter sets based on the two initial Poisson’s ratios of 0.45 and 0.49 as well as the pre- and unconditioned experimental responses, respectively. Our results highlight the close interrelation between the Poisson’s ratio and the remaining model parameters. The identified parameters will contribute to more precise computational models enabling spatially resolved predictions of the stress and strain states in human brains under complex mechanical loading conditions.<br

Inverse identification of region-specific hyperelastic material parameters for human brain tissue - Hinrichsen, Jan; Reiter, Nina; Bräuer, Lars; Paulsen, Friedrich; Käßmair, Stefan; Budday, Silvia (Biomechanics and modeling in mechanobiology, 2023)
The identification of material parameters accurately describing the region-dependent mechanical behavior of human brain tissue is crucial for computational models used to assist, e.g., the development of safety equipment like helmets or the planning and execution of brain surgery. While the division of the human brain into different anatomical regions is well established, knowledge about regions with distinct mechanical properties remains limited. Here, we establish an inverse parameter identification scheme using a hyperelastic Ogden model and experimental data from multi-modal testing of tissue from 19 anatomical human brain regions to identify mechanically distinct regions and provide the corresponding material parameters. We assign the 19 anatomical regions to nine governing regions based on similar parameters and microstructures. Statistical analyses confirm differences between the regions and indicate that at least the corpus callosum and the corona radiata should be assigned different material parameters in computational models of the human brain. We provide a total of four parameter sets based on the two initial Poisson’s ratios of 0.45 and 0.49 as well as the pre- and unconditioned experimental responses, respectively. Our results highlight the close interrelation between the Poisson’s ratio and the remaining model parameters. The identified parameters will contribute to more precise computational models enabling spatially resolved predictions of the stress and strain states in human brains under complex mechanical loading conditions.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Finite element method; Finite hyperelasticity; Human brain tissue; Ogden model; Parameter identification

JoVE Video Dataset - Polykandriotis, Elias; Himmler, Marcus; Mansouri, Shirin; Ruppe, Florian; Grüner, Jasmin; Bräuer, Lars; Schubert, Dirk W.; Horch, Raymund E. (2022)
With the evolution of suture materials, there has been a change in paradigms in primary and secondary tendon repair. Improved mechanical properties allow more aggressive rehabilitation and earlier recovery. However, for the repair to hold against higher mechanical demands, more advanced suturing and knotting techniques must be assessed in combination with those materials. In this protocol, the use of polytetrafluoroethylene (PTFE) as a suture material in combination with different repair techniques was investigated. In the first part of the protocol, both linear tension strength and elongation of knotted against not-knotted strands of three different materials used in flexor tendon repair were evaluated. The three different materials are polypropylene (PPL), ultra-high molecular weight polyethylene with a braided jacket of polyester (UHMWPE), and polytetrafluoroethylene (PTFE). In the next part (ex vivo experiments with cadaveric flexor tendons), the behavior of PTFE using different suture techniques was assessed and compared with PPL and UHMWPE. This experiment is comprised of four steps: harvesting of the flexor tendons from fresh cadaveric hands, transection of the tendons in a standardized manner, tendon repair by four different techniques, mounting, and measurement of the tendon repairs on a standard linear dynamometer. The UHMWPE and PTFE showed comparable mechanical properties and were significantly superior to PPL in terms of linear traction strength. Repairs with four- and six-strand techniques proved stronger than two-strand techniques. Handling and knotting of PTFE are a challenge due to very low surface friction but fastening of the four- or six-strand repair is comparatively easy to achieve. Surgeons routinely use PTFE suture material in cardiovascular surgery and breast surgery. The PTFE strands are suitable for use in tendon surgery, providing a robust tendon repair so that early active motion regimens for rehabilitation can be applie
Keywords: Polytetrafluoroethylene; PTFE; Suture Material; Tendon Surgery; Mechanical Properties; Flexor Tendon Repair; Linear Tension Strength; Cadaveric Upper Limb; Incision; A1 Pulley; Flexor Digitorum Profundus; Tendon Retractor; Traction

Morphological Evidence for a Unique Neuromuscular Functional Unit of the Human Vocalis Muscle - Tracicaru, Rareș Vasile; Bräuer, Lars; Döllinger, Michael; Schicht, Martin; Tillmann, Bernhard; Hînganu, Delia; Hristian, Liliana; Hînganu, Marius Valeriu; Paulsen, Friedrich (International Journal of Molecular Sciences, 2024)
Human vocalization is a complex process that is still only partially understood. Previous studies have suggested the possibility of a localized neuromuscular network of the larynx. Here we investigate this structure in human dissection specimens using multiple immunofluorescence and transmission electron microscopy (TEM). In the area of the pars interna of the thyroarytenoid muscle, muscle fibers are present that are clearly differentiated from skeletal or cardiac muscle cells and show an intermediate ultrastructure. In addition, intramuscular neurons are present that are detectable by both electron and fluorescence microscopy and may have a sensory function in a local neuronal network. Also, several types of sensory and motor synapses are detectable and distributed throughout the pars interna of the thyroarytenoid muscle, with multisynaptic muscle fibers being a common feature. These findings suggest the existence of a previously unrecognized type of muscle fiber coupled to an intramuscular neuronal network, the presence of which could explain functional peculiarities at the laryngeal level.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electron microscopy; immunofluorescence; laryngeal muscles; laryngeal nerves; larynx; neural network; neurolaryngology; neuromuscular junctions; synapses; voice formation

Muscular and neuronal control of voice production – forgotten findings, current concepts, and new developments - Tracicaru, Rares; Bräuer, Lars; Döllinger, Michael; Hînganu, Delia; Paulsen, Friedrich; Hînganu, Marius Valeriu (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Voice production has been an area of interest in science since ancient times, and although advancing research has improved our understanding of the anatomy and function of the larynx, there is still little general consensus on these two topics. This review aims to outline the main developments in this field and highlight the areas where further research is needed. The most important hypotheses are presented and discussed highlighting the four main lines of research in the anatomy of the human larynx and their most important findings: (1) the arrangement of the muscle fibers of the thyroarytenoid muscle is not parallel to the vocal folds in the internal part (vocalis muscle), leading to altered properties during contraction; (2) the histological structure of the human vocal cords differs from other striated muscles; (3) there is a specialized type of heavy myosin chains in the larynx; and (4) the neuromuscular system of the larynx has specific structures that form the basis of an intrinsic laryngeal nervous system. These approaches are discussed in the context of current physiological models of vocal fold vibration, and new avenues of investigation are proposed.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Intramuscular ganglia; Larynx; Muscle spindle; Myosin heavy chain; Neuromuscular junctions; Vocal fold oscillation; Voice

New insights into lacrimal gland anatomy using 7T MRI and electron microscopy: Relevance for lacrimal gland targeted therapies and bioengineering - Singh, Swati; Winter, Zoltan; Necker, Fabian; Bäuerle, Tobias; Scholz, Michael; Bräuer, Lars; Paulsen, Friedrich (Ocular Surface, 2023)
Purpose: To study the tissue architecture, isthmus (connection between two lobes) of the lacrimal gland using preclinical 7T MRI in combination with histology and electron microscopy. Methods: Ten lacrimal glands from Caucasian body donors (mean age 78.7 years) were studied using 7T-MRI (N = 5; scanned at 75-μm intervals), histology, and electron microscopy (N = 5) and 3D cinematic rendering (CR) techniques. Results: 3D CR images showed uniform-sized lobules (widest lobule diameter, 1.68 ± 0.19 mm in orbital lobe, 1.68 ± 0.17 mm in palpebral lobe) in both lobes, separated by septae (size, 0.29 ± 0.09 mm). The internal framework of the gland resembled a honeycoomb pattern. In CR and histology, the isthmus contained glandular acini, large blood vessels, nerves, and no more than two ducts having a tortuous course towards the conjunctival surface. On assigning a color display to the rendered lacrimal gland, all glands showed a blood vessel originating from the main lacrimal artery just 5 mm beyond the hilum and making it course to the palpebral lobe via isthmus. The distance between the conjunctiva and the central substance of the orbital and palpebral lobe was 9.4 ± 0.2 mm and 2.8 ± 0.7 mm, respectively. Electron microscopy of the palpebral lobe revealed compact subepithelial layer in the overlying conjunctiva, followed by loosely scattered collagen bundles that contained the gland lobules. Conclusion: 3D-CR can be used to study the lacrimal gland microstructure, help fabricate a 3D scaffold for lacrimal gland bioprinting, and serve as guide for transconjunctival lacrimal gland targeted therapies i.e., 2.9 & 9 mm long needle to reach the orbital and palpebral lobe center, respectively in normal-size glands.
CRIS-Team Scopus Importer:2023-10-13
Keywords: 3D printing; 7T MRI; Cinematic rendering; Dry eye disease; Lacrimal gland; Palpebral lobe

New insights into the lacrimal pump - Ali, Mohammad Javed; Zetzsche, Maximilian; Scholz, Michael; Hahn, Dieter; Gaffling, Simone; Heichel, Jens; Hammer, Christian; Bräuer, Lars; Paulsen, Friedrich (Ocular Surface, 2020)
Purpose: To date, there are many theories about tear transport through the canaliculi of the draining lacrimal system into the lacrimal sac but only few with supportive data. It is certain that the function of the lacrimal part of orbicularis oculi muscle (Horner-Duverney's muscle) is indispensable for the transport of “used” tears. However, the muscle's exact structure and the mechanisms of its functions are as yet unclear. To obtain deeper insights we undertook the present study. Methods: Upper and lower canaliculi (including the entrance into the lacrimal sac) from donor cadavers were dissected. Some of the specimens were prepared for scanning electron microscopy (SEM) to analyze the course of muscle fibers surrounding the canaliculi. Others were sectioned for enzyme- (EHC) and immunohistochemistry (IHC) to learn about the distribution of slow and fast reacting muscle fibers in Horner-Duverney's muscle as well as to analyze the distribution of different neurotransmitters to learn more about the innervation of Horner-Duverney's muscle. Four tear duct systems taken from body donors were cut out en bloc after formalin fixation, serially sectioned and reconstructed using a newly developed technology for 3D reconstruction of histological serial sections named HiD® (Chimaera GmbH, Germany). Patients that had undergone dacryocystorhinostomy (DCR) were video-analyzed endonasally during active blinking, focusing on viewing the temporal wall of the lacrimal sac movement where the canaliculi penetrated the lacrimal sac. Results: SEM revealed that muscle fibers of Horner-Duverney's muscle surround the vertical parts of the upper and lower canaliculus in a scissor like pattern whereas they ran in parallel to the first two thirds of the horizontal parts surrounding the respective canaliculus. Here, the muscle fibers were embedded in dense connective tissue forming a unique network. At the nasal third, muscle fibers left the canaliculi and ran to the posterior part of the fascia of the lacrimal sac and the lacrimal bone. EHC revealed that Horner-Duverney's muscle contained nearly an equal distribution of type I and type IIb muscle fibers compared to the superior rectus muscle which contains more type I and the masseter and iliopsoas muscles with more type IIb muscle fibers. IHC indicated presence of trigeminal, catecholaminergic and cholinergic nerve endings. 3D reconstructions supported the SEM data. Endonasal video analysis of patients after DCR with a nasally open lacrimal sac revealed bulging of the temporal wall of the lacrimal sac during blinking. On the basis of these findings, a modified lacrimal pump theory is proposed. Conclusion: The results support the hypothesis that contraction of Horner-Duverney's muscle leads to closure of the canaliculi in their first two thirds based on the special arrangement of muscle fibers and connective tissue fibers. This causes the tear fluid in the canaliculi to be pressed/transported towards the lacrimal sac. The medial third of the vertical portions of the canaliculi, the canaliculus communis and the intrasaccal portion of the canaliculus are compressed by the shortening and thickening of the Horner-Duverney muscle from dorsal, which leads to a compression of the canaliculi lumens in this part of the system, thereby pushing the lacrimal fluid further towards the lacrimal sac. The mix of fast contracting and fatigue resistant muscle fibers is ideally suited for the blink mechanism that is complexly regulated by the nervous system.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Canaliculus; Efferent tear ducts; Horner's muscle; Lacrimal pump; Nasolacrimal ducts; Orbicularis oculi; Tear drainage; Tear flow

Optical imaging techniques in engineering thermodynamics - Bräuer, Lars; Zigan, Lars; Fröba, Andreas Paul; Wensing, Michael; Leipertz, Alfred; Will, Stefan (Kick-off Symposium Optical Imaging Center Erlangen, 2013)

Palate Lung Nasal Clone (PLUNC), a Novel Protein of the Tear Film: Three-Dimensional Structure, Immune Activation, and Involvement in Dry Eye Disease (DED) - Schicht, Martin; Rausch, Felix; Beron, Martin; Jacobi, Christina; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Kruse, Friedrich; Bräuer, Lars; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2015)
Palate Lung Nasal Clone (PLUNC) is a hydrophobic protein belonging to the family of surfactant proteins that is involved in fluid balance regulation of the lung. Moreover, it is known to directly act against gram-negative bacteria. The purpose of this study was to investigate the possible expression and antimicrobial role of PLUNC at the healthy ocular surface and in tears of patients suffering from dry eye disease (DED).Bioinformatics and biochemical and immunologic methods were combined to elucidate the structure and function of PLUNC at the ocular surface. Tissue-specific localization was performed by using immunohistochemistry. The PLUNC levels in tear samples from non-Sjögren's DED patients with moderate dry eye suffering either from hyperevaporation or tear deficiency were analyzed by ELISA and compared with tears from healthy volunteers.Palate Lung Nasal Clone is expressed under healthy conditions at the ocular surface and secreted into the tear film. Protein modeling studies and molecular dynamics simulations performed indicated surface activity of PLUNC. In vitro experiments revealed that proinflammatory cytokines and bacterial supernatants have only a slight effect on the expression of PLUNC in HCE and HCjE cell lines. In tears from DED patients, the PLUNC concentration is significantly increased (7-fold in evaporative dry eye tears and 17-fold in tears from patients with tear deficiency) compared with healthy subjects.The results show that PLUNC is a protein of the tear film and suggest that it plays a role in fluid balance and surface tension regulation at the ocular surface.
EVALuna2:4442

Personalized Chest Computed Tomography: Minimum Diagnostic Radiation Dose Levels for the Detection of Fibrosis, Nodules, and Pneumonia - May, Matthias; Heiß, Rafael; Köhnen, Julia; Wetzl, Matthias; Wiesmüller, Marco; Treutlein, Christoph; Uder, Michael; Kopp, Markus; Bräuer, Lars (Investigative Radiology, 2022)
OBJECTIVES: The purpose of this study was to evaluate the minimum diagnostic radiation dose level for the detection of high-resolution (HR) lung structures, pulmonary nodules (PNs), and infectious diseases (IDs). MATERIALS AND METHODS: A preclinical chest computed tomography (CT) trial was performed with a human cadaver without known lung disease with incremental radiation dose using tin filter-based spectral shaping protocols. A subset of protocols for full diagnostic evaluation of HR, PN, and ID structures was translated to clinical routine. Also, a minimum diagnostic radiation dose protocol was defined (MIN). These protocols were prospectively applied over 5 months in the clinical routine under consideration of the individual clinical indication. We compared radiation dose parameters, objective and subjective image quality (IQ). RESULTS: The HR protocol was performed in 38 patients (43%), PN in 21 patients (24%), ID in 20 patients (23%), and MIN in 9 patients (10%). Radiation dose differed significantly among HR, PN, and ID (5.4, 1.2, and 0.6 mGy, respectively; P < 0.001). Differences between ID and MIN (0.2 mGy) were not significant (P = 0.262). Dose-normalized contrast-to-noise ratio was comparable among all groups (P = 0.087). Overall IQ was perfect for the HR protocol (median, 5.0) and decreased for PN (4.5), ID-CT (4.3), and MIN-CT (2.5). The delineation of disease-specific findings was high in all dedicated protocols (HR, 5.0; PN, 5.0; ID, 4.5). The MIN protocol had borderline IQ for PN and ID lesions but was insufficient for HR structures. The dose reductions were 78% (PN), 89% (ID), and 97% (MIN) compared with the HR protocols. CONCLUSIONS: Personalized chest CT tailored to the clinical indications leads to substantial dose reduction without reducing interpretability. More than 50% of patients can benefit from such individual adaptation in a clinical routine setting. Personalized radiation dose adjustments with validated diagnostic IQ are especially preferable for evaluating ID and PN lesions.
CRIS-Team Scopus Importer:2022-02-25

Plasma gelsolin promotes re-epithelialization - Wittmann, Johannes; Dieckow, J.; Schröder, Henrik; Hampel, Ulrike; Garreis, Fabian; Jacobi, Christina; Milczarek, Aleksandra; Hsieh, K. L.; Pulli, Benjamin; Chen, J. W.; Hoogeboom, S.; Bräuer, Lars; et al. (Scientific Reports, 2018)
Woundhealing disorders characterized by impaired or delayed re-epithelialization are a serious medical problem that is painful and difficult to treat. Gelsolin (GSN), a known actin modulator, supports epithelial cell regeneration and apoptosis. The aim of this study was to estimate the potential of recombinant gelsolin (rhu-pGSN) for ocular surface regeneration to establish a novel therapy for delayed or complicated wound healing. We analyzed the influence of gelsolin on cell proliferation and wound healing in vitro, in vivo/ex vivo and by gene knockdown. Gelsolin is expressed in all tested tissues of the ocular system as shown by molecular analysis. The concentration of GSN is significantly increased in tear fluid samples of patients with dry eye disease. rhu-pGSN induces cell proliferation and faster wound healing in vitro as well as in vivo/ex vivo. TGF-β dependent transcription of SMA is significantly decreased after GSN gene knockdown. Gelsolin is an inherent protein of the ocular system and is secreted into the tear fluid. Our results show a positive effect on corneal cell proliferation and wound healing. Furthermore, GSN regulates the synthesis of SMA in myofibroblasts, which establishes GSN as a key protein of TGF-β dependent cell differentiation.
EVALuna2:35306

Polytetrafluoroethylene (PTFE) as a Suture Material in Tendon Surgery - Polykandriotis, Elias; Himmler, Marcus; Mansouri, Shirin; Ruppe, Florian; Grüner, Jasmin; Bräuer, Lars; Schubert, Dirk W.; Horch, Raymund E. (Journal of Visualized Experiments, 2022)
With the evolution of suture materials, there has been a change in paradigms in primary and secondary tendon repair. Improved mechanical properties allow more aggressive rehabilitation and earlier recovery. However, for the repair to hold against higher mechanical demands, more advanced suturing and knotting techniques must be assessed in combination with those materials. In this protocol, the use of polytetrafluoroethylene (PTFE) as a suture material in combination with different repair techniques was investigated. In the first part of the protocol, both linear tension strength and elongation of knotted against not-knotted strands of three different materials used in flexor tendon repair were evaluated. The three different materials are polypropylene (PPL), ultra-high molecular weight polyethylene with a braided jacket of polyester (UHMWPE), and polytetrafluoroethylene (PTFE). In the next part (ex vivo experiments with cadaveric flexor tendons), the behavior of PTFE using different suture techniques was assessed and compared with PPL and UHMWPE. This experiment is comprised of four steps: harvesting of the flexor tendons from fresh cadaveric hands, transection of the tendons in a standardized manner, tendon repair by four different techniques, mounting, and measurement of the tendon repairs on a standard linear dynamometer. The UHMWPE and PTFE showed comparable mechanical properties and were significantly superior to PPL in terms of linear traction strength. Repairs with four- and six-strand techniques proved stronger than two-strand techniques. Handling and knotting of PTFE are a challenge due to very low surface friction but fastening of the four- or six-strand repair is comparatively easy to achieve. Surgeons routinely use PTFE suture material in cardiovascular surgery and breast surgery. The PTFE strands are suitable for use in tendon surgery, providing a robust tendon repair so that early active motion regimens for rehabilitation can be applied.
CRIS-Team Scopus Importer:2022-11-18

Polytetrafluoroethylene (PTFE) suture vs fiberwire and polypropylene in flexor tendon repair - Polykandriotis, Elias; Ruppe, Florian; Niederkorn, Miriam; Polykandriotis, Ektor; Bräuer, Lars; Horch, Raymund E.; Arkudas, Andreas; Grüner, Johanna (Archives of Orthopaedic and Trauma Surgery, 2021)
Background In this study, we evaluate the value of novel suture material based on monofilamentous-extruded polyfluoroethylene (PTFE) compared to polypropylene (PPL) and Fiberwire (FW). Materials and methods 60 flexor tendons were harvested from fresh cadaveric upper extremities. 4-0 sutures strands were used in the PPL, FW and PTFE group. Knotting properties and mechanical characteristics of the suture materials were evaluated. A 4-strand locked cruciate (Adelaide) or a 6-strand (M-Tang) suture technique was applied as core sutures for a tendon repair. Two-way ANOVA tests were performed with the Bonferroni correction. Results Stable knotting was achieved with 5 throws with the PPL material, 7 throws for FW and 9 throws for PTFE. In the PPL group, linear tensile strength was 45.92 +/- 12.53 N, in the FW group 80.11 +/- 18.34 N and in the PTFE group 76.16 +/- 29.10 N. FW and PTFE are significantly stronger than PPL but show no significant difference among each other. Similar results were obtained in the subgroup comparisons for different repair techniques. The Adelaide and the M-Tang knotting technique showed no significant difference. Conclusion Fiberwire showed superior handling and knotting properties in comparison to PTFE. However, PTFE allows easier approximation of the stumps. In both, M-Tang and Adelaide repairs, PTFE was equal to FW in terms of repair strength. Both PTFE and FW provide for a robust tendon repair so that early active motion regimens for rehabilitation can be applied.
CRIS-Team WoS Importer:2021-05-07

Precision and effort in robot-assisted placement of pedicle screws compared to standard surgical navigation - Sippel, Julia Katharina; Groh, Johannes; Bräuer, Lars; Perl, Mario; Stadthalter, Holger (Scientific Reports, 2024)
Aim was to compare image-guided navigation with a robot-assisted solution for performing MISS regarding precision, required time and subjective aspects. 90 pedicles were instrumented on two torsos, half with navigation, half robot-assisted. Precision analysis between both solutions didn’t show a significant difference. Time measurement showed a significantly longer duration per wire for the robot-arm on the first torso and a not significant longer duration on the second torso, where a significant reduction in the mean duration was shown. There was no significant difference in the subjective impressions comparing navigation and robot except the possibility to change the procedure. Precision of both methods is suitable for clinical use. A time advantage using the robot-arm couldn’t be demonstrated in the present study. A significant learning curve was shown, so a reduction in the longer duration on the robot can be expected. Further studies in clinical use are necessary.
CRIS-Team Scopus Importer:2024-11-22

Protein modeling and molecular dynamics simulation of the two novel surfactant proteins SP-G and SP-H - Rausch, Felix; Schicht, Martin; Bräuer, Lars; Paulsen, Friedrich; Brandt, Wolfgang (Journal of Molecular Modeling, 2014)
Surfactant proteins are well known from the human lung where they are responsible for the stability and flexibility of the pulmonary surfactant system. They are able to influence the surface tension of the gas-liquid interface specifically by directly interacting with single lipids. This work describes the generation of reliable protein structure models to support the experimental characterization of two novel putative surfactant proteins called SP-G and SP-H. The obtained protein models were complemented by predicted posttranslational modifications and placed in a lipid model system mimicking the pulmonary surface. Molecular dynamics simulations of these protein-lipid systems showed the stability of the protein models and the formation of interactions between protein surface and lipid head groups on an atomic scale. Thereby, interaction interface and strength seem to be dependent on orientation and posttranslational modification of the protein. The here presented modeling was fundamental for experimental localization studies and the simulations showed that SP-G and SP-H are theoretically able to interact with lipid systems and thus are members of the surfactant protein family.
EVALuna2:4436

Quantification of surfactant proteins in tears of patients suffering from dry eye disease compared to healthy subjects - Posa, Andreas; Paulsen, Friedrich; Dietz, Richard; Garreis, Fabian; Sander, Ralph; Schicht, Martin; Sel, Saadettin; Scholz, Michael; Hammer, Christian; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2018)
PURPOSE: To quantify and compare the amounts of surfactant proteins SP-A, SP-B, SP-C and SP-D in the tear fluid collected from patients with dry eye syndrome and from individuals with a healthy ocular surface. METHODS: Schirmer strips were used to collect tear fluid from both eyes of 241 volunteers (99 men, 142 women; age range: 18-87 years). Dry eye syndrome was diagnosed by ophthalmologists in 125 patients, whereas the healthy control group comprised 116 individuals. The total protein concentration was determined via Bradford assay. The relative concentration of surfactant proteins SP-A through -D was measured by enzyme-linked immuno-sorbent assay (ELISA). RESULTS: The mean relative concentrations of SP-A, SP-C and SP-D were significantly higher in the dry eye group as compared to the healthy controls (p<0.05, one-way ANOVA). SP-B was also detected at a higher concentration in the dry eye group, but the difference to the control group was not statistically significant. CONCLUSIONS: The upregulation of SP-A and SP-D in the dry eye group is probably related to these proteins' known antimicrobial and immunomodulatory effects at the ocular surface. It may represent a pathophysiological response to the inflammatory condition of the ocular surface in dry eye. The upregulation of SP-B and SP-C may represent an effort of the lacrimal system to reduce surface tension and thus to counteract the increased tendency of the tear film to tear in dry eye.
EVALuna2:35321

Recombinant expression of surfactant protein H (SFTA3) in Escherichia coli - Schröder, Henrik; Sollfrank, L.; Paulsen, Friedrich; Bräuer, Lars; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2016)
Surfactant proteins are broadly understood to be an important structural and functional part of the lung surfactant system. These proteins influence the intra-alveolar surface tension and contribute to innate immunity of the lung. Beside the four already known surfactant proteins SP-A, SP-B, SP-C and SP-D, two novel SPs (SP-G/SFTA2 and SP-H/SFTA3) have recently been described. These show no sequential or structural similarity with the already known SPs. However, bioinformatic prediction tools suggest physicochemical properties, which have already been described for other surfactant proteins. Although it is known that SFTA2 and SFTA3 are expressed in different human tissues, their distinct functional properties remain unclear. Here, we describe the establishment of a stable expression system for recombinant SFTA3 protein synthesis in Escherichia coli. This gives rise to future experiments with the overall aim to further examine and characterize this novel protein in more detail.
EVALuna2:34493

Recommendations of the working group of the Anatomische Gesellschaft on reduction of formaldehyde exposure in anatomical curricula and institutes - Waschke, Jens; Bergmann, Martin; Bräuer, Lars; Brenner, Erich; Buchhorn, Andreas; Deutsch, Arlette; Dokter, Martin; Egu, Desalegn Tadesse; Erguen, Suelleyman; Fassnacht, Ulrich; Fietz, Daniela; Gundlach, Stefanie; et al. (Annals of Anatomy-Anatomischer Anzeiger, 2019)
The practice of human and veterinary medicine is based on the science of anatomy and dissection courses are still irreplaceable in the teaching of anatomy. Embalming is required to preserve body donors, for which process formaldehyde (FA) is the most frequently used and well characterized biocidal substance. Since January 2016, a new occupational exposure limit (OEL) for FA of 0.37 mg/m(3) issued by the European Committee on Hazardous Substances is obligatory since FA has been classified as a human 1B carcinogen. The anatomical institutes in the German-speaking region are called upon to consolidate efforts to reduce use of FA in anatomical curricula and body donations. As a result, the Anatomische Gesellschaft (AG) has formed a "Working Group for Reduction of Formaldehyde Exposure in Dissection Courses" tasked with discussion and recommendation of measures to reduce FA. Based on the assessment of the Working Group, the AG has issued an official opinion to the effect that, at this point in time, embalming of body donors without FA completely is not feasible. Therefore, a combination of approaches are to be used to reduce FA exposure, including technical and structural (architectural) adaptations, modification of protocols for fixation and preservation as well as organizational measures. One structural measure considered unavoidable is the integration of air supply and exhaust of individual dissecting tables into the ventilation system of the anatomy building. To embalm human body donors, intra-arterial perfusion fixation with up to 4% FA and a total fluid volume of 150 mL/kg body weight will suffice. For animals where body weights and biology of bodies vary widely (i.e. special needs of fixation for ruminants, large animals as horses) perfusion fixation with up to 4% FA and a quantity of fixative solution of 10-15% of the body weight may be required. Preservation of body donors in storage (immersion) can be done with 40% ethanol or in a full bath preservation containing up to 2% FA. Corpse humidification in the dissecting room is possible with 2% phenoxyethanol, in each case without FA. In veterinary anatomy, microbiological burden is often higher and therefore might lead to a need of FA in long-time storage. Compliance with the current OEL in all institutes would appear to be feasible in combination with various organizational measures. (C) 2018 Elsevier GmbH. All rights reserved.
CRIS-Team WoS Importer:2019-03-01

SFTA3, a novel protein of the lung: three-dimensional structure, characterisation and immune activation - Schicht, Martin; Rausch, Felix; Finotto, Susetta; Mathews, Martina; Mattil, Anja; Schubert, Melanie; Koch, Beate; Traxdorf, Maximilian; Bohr, Christopher; Worlitzsch, Dieter; Brandt, Wolfgang; Garreis, Fabian; et al. (European Respiratory Journal, 2014)
The lung constantly interacts with numerous pathogens. Thus, complex local immune defence mechanisms are essential to recognise and dispose of these intruders. This work describes the detection, characterisation and three-dimensional structure of a novel protein of the lung (surfactant-associated protein 3 (SFTA3/SP-H)) with putative immunological features. Bioinformatics, biochemical and immunological methods were combined to elucidate the structure and function of SFTA3. The tissue-specific detection and characterisation was performed by using electron microscopy as well as fluorescence imaging. Three-dimensional structure generation and analysis led to the development of specific antibodies and, as a consequence, to the localisation of a novel protein in human lung under consideration of cystic fibrosis, asthma and sepsis. In vitro experiments revealed that lipopolysaccharide induces expression of SFTA3 in the human lung alveolar type II cell line A549. By contrast, the inflammatory cytokines interleukin (IL)-1? and IL-23 inhibit expression of SFTA3 in A549. Sequence- and structure-based prediction analysis indicated that the novel protein is likely to belong to the family of lung surfactant proteins. The results suggest that SFTA3 is an immunoregulatory protein of the lung with relevant protective functions during inflammation at the mucosal sites.
EVALuna2:4400

SFTA3 - a novel surfactant protein of the ocular surface and its role in corneal wound healing and tear film surface tension - Schicht, Martin; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Jacobi, Christina; Sahin, Afsun; Holland, Detlef; Schröder, Henrik; Hammer, Christian; Paulsen, Friedrich; Bräuer, Lars (Scientific Reports, 2018)
The study aimed to characterize the expression and function of SFTA3 at the ocular surface and in tears. Ocular tissues, conjunctival (HCjE) and human corneal (HCE) epithelial cell lines as well as tearfilm of patients suffering from different forms of dry eye disease (DED) were analyzed by means of RT-PCR, western blot, immunohistochemistry, and ELISA. A possible role of recombinant SFTA3 in corneal wound healing was investigated performing in vitro scratch assays. Tear film regulatory properties were analyzed with the spinning drop method and the regulation of SFTA3 transcripts was studied in HCE and HCjE after incubation with proinflammatory cytokines as well as typical ocular pathogens by real-time RT-PCR and ELISA. The results reveal that human ocular tissue as well as tears of healthy volunteers express SFTA3 whereas tears from patients with DED showed significantly increased SFTA3 levels. In vitro wounding of HCE cell cultures that had been treated with recombinant SFTA3 demonstrated a significantly increased wound closure rate and rSFTA3 reduced the surface tension of tear fluid. The results indicate that SFTA3 at the ocular surface seemed to be involved in wound healing and the reduction of surface tension.
EVALuna2:35316

Somatostatin supports corneal wound healing in vivo - Hampel, Ulrike; Frömmling, Paul; Bräuer, Lars; Schaefer, Ivonne; Sel, Saadettin; Holland, Detlev; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: To evaluate the influence of somatostatin (SST) and its analog octreotid (Oct) on corneal wound healing processes. METHODS: The wound healing rate in C57BL/6 mice eyes under SST and Oct treatment was analyzed using an alkali-induced corneal wounding model. Effects of SST and Oct on cell proliferation, migration and quantified protein expression of vascular endothelial growth factor (VEGF) on human corneal epithelial cells (HCE, cell line) were evaluated by means of electric cell-substrate impedance sensing, scratch migration assays and ELISA. ERK1/2 and p38 phosphorylation was investigated by semi-quantitative western blot analysis. RESULTS: Ten nanograms per microliters of SST significantly accelerated the wound closure rate of corneal defects in vivo. SST and Oct had no influence on HCE cell proliferation and migration and did not activate ERK1/2 or p38 signaling in HCE cells. However, there was increased VEGF protein expression in cytosolic proteins and medium supernatants of HCE upon Oct stimulation for 24h. One and 10ng/ml Oct led to a 2.5-fold and 100ng/ml Oct to a 4-fold upregulation of VEGF protein expression. CONCLUSION: The data implicate that SST promotes corneal wound healing in a mouse model. However, using a HCE cell line in vitro, the wound healing mechanism does not seem to be supported by proliferation and migration processes or by activation of ERK1/2 and p38 signaling pathways. Other possible mechanisms could be the activation of other pathways and the induction of growth factors such as VEGF that modulate the observed corneal wound healing process.
EVALuna2:34494

SP-G, a novel surfactant protein of the ocular surface that regulates surface tension of tears and might play a role in dry eye disease - Bräuer, Lars; Schicht, Martin; Paulsen, Friedrich (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

"SP-G", a Putative New Surfactant Protein - Tissue Localization and 3D Structure - Rausch, Felix; Schicht, Martin; Paulsen, Friedrich; Ngueya, Ivan; Bräuer, Lars; Brandt, Wolfgang (PLoS ONE, 2012)
Surfactant proteins (SP) are well known from human lung. These proteins assist the formation of a monolayer of surface-active phospholipids at the liquid-air interface of the alveolar lining, play a major role in lowering the surface tension of interfaces, and have functions in innate and adaptive immune defense. During recent years it became obvious that SPs are also part of other tissues and fluids such as tear fluid, gingiva, saliva, the nasolacrimal system, and kidney. Recently, a putative new surfactant protein (SFTA2 or SP-G) was identified, which has no sequence or structural identity to the already know surfactant proteins. In this work, computational chemistry and molecular-biological methods were combined to localize and characterize SP-G. With the help of a protein structure model, specific antibodies were obtained which allowed the detection of SP-G not only on mRNA but also on protein level. The localization of this protein in different human tissues, sequence based prediction tools for posttranslational modifications and molecular dynamic simulations reveal that SP-G has physicochemical properties similar to the already known surfactant proteins B and C. This includes also the possibility of interactions with lipid systems and with that, a potential surface-regulatory feature of SP-G. In conclusion, the results indicate SP-G as a new surfactant protein which represents an until now unknown surfactant protein class. © 2012 Rausch et al.
CRIS-Team Scopus Importer:2022-08-05

Staphylococcus aureus and Pseudomonas aeruginosa Express and Secrete Human Surfactant Proteins - Schicht, Martin; Worlitzsch, Dieter; Bensel, Tobias; Sawers, R. Gary; Paulsen, Friedrich; Bräuer, Lars (PLoS ONE, 2013)
Surfactant proteins (SP), originally known from human lung surfactant, are essential to proper respiratory function in that they lower the surface tension of the alveoli. They are also important components of the innate immune system. The functional significance of these proteins is currently reflected by a very large and growing number of publications. The objective goal of this study was to elucidate whether Staphylococcus aureus and Pseudomonas aeruginosa is able to express surfactant proteins. 10 different strains of S. aureus and P. aeruginosa were analyzed by means of RT-PCR, Western blot analysis, ELISA, immunofluorescence microscopy and immunoelectron microscopy. The unexpected and surprising finding revealed in this study is that different strains of S. aureus and P. aeruginosa express and secrete proteins that react with currently commercially available antibodies to known human surfactant proteins. Our results strongly suggest that the bacteria are either able to express 'human-like' surfactant proteins on their own or that commercially available primers and antibodies to human surfactant proteins detect identical bacterial proteins and genes. The results may reflect the existence of a new group of bacterial surfactant proteins and DNA currently lacking in the relevant sequence and structure databases. At any rate, our knowledge of human surfactant proteins obtained from immunological and molecular biological studies may have been falsified by the presence of bacterial proteins and DNA and therefore requires critical reassessment. © 2013 Bräuer et al.
CRIS-Team Scopus Importer:2022-08-05

Strategies against Burnout and Anxiety in Medical Education - Implementation and Evaluation of a New Course on Relaxation Techniques (Relacs) for Medical Students - Wild, Katharina; Scholz, Michael; Ropohl, Axel; Bräuer, Lars; Paulsen, Friedrich; Burger, Pascal H. M. (PLoS ONE, 2014)
Burnout and stress-related mental disorders (depression, anxiety) occur in medical students and physicians with a significantly higher prevalence than in the general population. At the same time, the learning of coping mechanisms against stress is still not an integral part of medical education. In this pilot study we developed an elective course for learning relaxation techniques and examined the condition of the students before and after the course. 42 students participated in the semester courses in 2012 and 2013 as well as in a survey at the start and end of each course. The students were instructed in autogenic training (AT) and progressive muscle relaxation according to Jacobsen (PMR) with the goal of independent and regular exercising. At the beginning and the end of the semester/course the students were interviewed using standardized, validated questionnaires on burnout (BOSS-II) and anxiety (STAI-G), depression (BDI), quality of life (SF-12) and sense of coherence (SOC-L9). We compared the results of our students participating in Relacs with results from eight semester medical students (n = 88), assessed with the same questionnaires at similar points of time within their semester. Participating students showed a significant decline in cognitive and emotional burnout stress and in trait anxiety. Furthermore, they showed a reduction in state anxiety and a conspicuous decrease in mean depression. The sense of coherence increased at the same time. A comparative cohort of medical students of 8th semester students, showed lower values for the specified measurement parameters at the beginning, but showed no progressive changes. Our course introducing AT and PMR led to a significant reduction of burnout and anxiety within the participating group of medical students. Even the course attendance for just one semester resulted in significant improvements in the evaluated parameters in contrast to those students who did not attend the course.
EVALuna2:4405

Surfactant protein H is part of the tear film, lowers surface tension, is increased in dry eye disease and accelerates corneal wound healing - Paulsen, Friedrich; Hartjen, Nadine; Beilicke, Stephanie; Garreis, Fabian; Jacobi, Christina; Sahin, Afsun; Holland, Detlev; Bräuer, Lars; Schicht, Martin (2018)
EVALuna2:35310

Surfactant proteins of the human larynx - Sheats, Michelle; Schröder, Henrik; Rauscha, F.; Bohr, Christopher; Kißlinger, Franziska; De Tristan, J.; Iro, Heinrich; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: Surfactant proteins (SPs) originally identified in lung tissue are important players in the innate immune system. Beyond this, they contribute to stability and rheology of gaseous or aqueous interphases. In the present study, we determined the expression and presence of SPs (A, B, C and D) in different areas of the human larynx. METHODS: mRNA expression of SP-A, -B, -C and -D was analyzed by means of RT-PCR in healthy samples of epiglottis, vocal and vestibular folds, subglottis and trachea. Distribution and localization of all four SPs were analyzed by Western blot and immunohistochemistry in healthy human tissue samples. RESULTS: All four SPs were detected at the mRNA- and protein level in the human larynx as well as by means of immunohistochemistry in the different tissue samples of the human larynx. CONCLUSION: The results reveal that all four SPs are produced with different expression patterns within the human larynx. Based on the known functions, our results suggest that SPs might be involved in maintaining mucus rheology and subsequently they could be essential components for proper phonation. Moreover, the proteins seem to play a role in immune defense of the larynx.
EVALuna2:33358

The Cerebral Surfactant System and Its Alteration in Hydrocephalic Conditions - Schob, Stefan; Lobsien, Donald; Friedrich, Benjamin; Bernhard, Matthias K.; Gebauer, Corinna; Dieckow, Julia; Gawlitza, Matthias; Pirlich, Mandy; Saur, Dorothee; Bräuer, Lars; Bechmann, Ingo; Hoffmann, Karl-Titus; et al. (PLoS ONE, 2016)
INTRODUCTION: Pulmonary Surfactant reduces surface tension in the terminal airways thus facilitating breathing and contributes to host's innate immunity. Surfactant Proteins (SP) A, B, C and D were recently identified as inherent proteins of the CNS. Aim of the study was to investigate cerebrospinal fluid (CSF) SP levels in hydrocephalus patients compared to normal subjects. PATIENTS AND METHODS: CSF SP A-D levels were quantified using commercially available ELISA kits in 126 patients (0-84 years, mean 39 years). 60 patients without CNS pathologies served as a control group. Hydrocephalus patients were separated in aqueductal stenosis (AQS, n = 24), acute hydrocephalus without aqueductal stenosis (acute HC w/o AQS, n = 16) and idiopathic normal pressure hydrocephalus (NPH, n = 20). Furthermore, six patients with pseudotumor cerebri were investigated. RESULTS: SP A-D are present under physiological conditions in human CSF. SP-A is elevated in diseases accompanied by ventricular enlargement (AQS, acute HC w/o AQS) in a significant manner (0.67, 1.21 vs 0.38 ng/ml in control, p<0.001). SP-C is also elevated in hydrocephalic conditions (AQS, acute HC w/o AQS; 0.87, 1.71 vs. 0.48 ng/ml in controls, p<0.001) and in Pseudotumor cerebri (1.26 vs. 0.48 ng/ml in controls, p<0.01). SP-B and SP-D did not show significant alterations. CONCLUSION: The present study confirms the presence of SPs in human CSF. There are significant changes of SP-A and SP-C levels in diseases affecting brain water circulation and elevation of intracranial pressure. Cause of the alterations, underlying regulatory mechanisms, as well as diagnostic and therapeutic consequences of cerebral SP's requires further thorough investigations.
EVALuna2:34490

The chemicals between us—First results of the cluster analyses on anatomy embalming procedures in the German-speaking countries - Kerner, Alexander Michael; Biedermann, Uta; Bräuer, Lars; Caspers, Svenja; Doll, Sara; Engelhardt, Maren; Filler, Timm J.; Ghebremedhin, Estifanos; Gundlach, Stefanie; Hayn-Leichsenring, Gregor U.; Heermann, Stephan; Hettwer-Steeger, Ingrid; et al. (Anatomical Sciences Education, 2023)
Hands-on courses utilizing preserved human tissues for educational training offer an important pathway to acquire basic anatomical knowledge. Owing to the reevaluation of formaldehyde limits by the European Commission, a joint approach was chosen by the German-speaking anatomies in Europe (Germany, Austria, Switzerland) to find commonalities among embalming protocols and infrastructure. A survey comprising 537 items was circulated to all anatomies in German-speaking Europe. Clusters were established for “ethanol”-, formaldehyde-based (“FA”), and “other” embalming procedures, depending on the chemicals considered the most relevant for each protocol. The logistical framework, volumes of chemicals, and infrastructure were found to be highly diverse between the groups and protocols. Formaldehyde quantities deployed per annum were three-fold higher in the “FA” (223 L/a) compared to the “ethanol” (71.0 L/a) group, but not for “other” (97.8 L/a), though the volumes injected per body were similar. “FA” was strongly related to table-borne air ventilation and total fixative volumes ≤1000 L. “Ethanol” was strongly related to total fixative volumes >1000 L, ceiling- and floor-borne air ventilation, and explosion-proof facilities. Air ventilation was found to be installed symmetrically in the mortuary and dissection facilities. Certain predictors exist for the interplay between the embalming used in a given infrastructure and technical measures. The here-established cluster analysis may serve as decision supportive tool when considering altering embalming protocols or establishing joint protocols between institutions, following a best practice approach to cater toward best-suited tissue characteristics for educational purposes, while simultaneously addressing future demands on exposure limits.
CRIS-Team Scopus Importer:2023-05-26
Keywords: body donor; cadaver; conservation; embalming; fixation; formaldehyde; human tissue; occupational exposure limit the value

The Detection of Surfactant Proteins A, B, C and D in the Human Brain and Their Regulation in Cerebral Infarction, Autoimmune Conditions and Infections of the CNS - Schob, Stefan; Schicht, Martin; Sel, Saadettin; Stiller, Dankwart; Kekule, Alexander; Paulsen, Friedrich; Maronde, Erik; Bräuer, Lars (PLoS ONE, 2013)
Surfactant proteins (SP) have been studied intensively in the respiratory system. Surfactant protein A and surfactant protein D are proteins belonging to the family of collectins each playing a major role in the innate immune system. The ability of surfactant protein A and surfactant protein D to bind various pathogens and facilitate their elimination has been described in a vast number of studies. Surfactant proteins are very important in modulating the host's inflammatory response and participate in the clearance of apoptotic cells. Surfactant protein B and surfactant protein C are proteins responsible for lowering the surface tension in the lungs. The aim of this study was an investigation of expression of surfactant proteins in the central nervous system to assess their specific distribution patterns. The second aim was to quantify surfactant proteins in cerebrospinal fluid of healthy subjects compared to patients suffering from different neuropathologies. The expression of mRNA for the surfactant proteins was analyzed with RT-PCR done with samples from different parts of the human brain. The production of the surfactant proteins in the brain was verified using immunohistochemistry and Western blot. The concentrations of the surfactant proteins in cerebrospinal fluid from healthy subjects and patients suffering from neuropathologic conditions were quantified using ELISA. Our results revealed that surfactant proteins are present in the central nervous system and that the concentrations of one or more surfactant proteins in healthy subjects differed significantly from those of patients affected by central autoimmune processes, CNS infections or cerebral infarction. Based on the localization of the surfactant proteins in the brain, their different levels in normal versus pathologic samples of cerebrospinal fluid and their well-known functions in the lungs, it appears that the surfactant proteins may play roles in host defense of the brain, facilitation of cerebrospinal fluid secretion and maintenance of the latter's rheological properties. © 2013 Schob et al.
CRIS-Team Scopus Importer:2022-08-05

The distribution of human surfactant proteins within the oral cavity and their role during infectious diseases of the gingiva - Schicht, Martin; Stengl, Christina; Sel, Sadettin; Heinemann, Friedhelm; Goetz, Werner; Petschelt, Anselm; Pelka, Matthias; Scholz, Michael; Rausch, Felix; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2015)
The oral cavity with the teeth and the surrounding gingival epithelium, the periodontium, the salivary glands and other structures are open to the oral environment and thus exposed to multiple microbiological and pathogenic influences. To prevent permanent inflammatory processes such as gingivitis or periodontitis an efficient defense system is essential to ensure healthy and physiological function of the oral cavity and other interacting organic systems. Surfactant proteins (SPs), originally found in pulmonary tissue are important factors of the immune system and beyond this, support the stability and rheology of gas or fluid interfaces. This study aimed to analyze the distribution of surfactant proteins by means of Western blot and immunohistochemistry in salivary glands as well as in healthy and pathological saliva. The different expression patterns of SP-A, -B, -C and -D in healthy and pathological (periodontitis) saliva were determined using ELISA quantification. One further objective of the study was the first detection of two recent discovered proteins belonging to the surfactant protein family within human salivary glands and saliva. The results of the study reveal differences in protein expression of SP-A, -B, -C and -D within healthy and pathologic saliva. The concentration of the surfactant proteins SP-A, SP-C and SP-D is increased in saliva of people suffering from periodontal diseases, whereas by contrast, SP-B shows an opposite expression pattern. Furthermore, the results evidence the presence of SP-G and SP-H within saliva and salivary glands for the first time.
EVALuna2:4399

The novel surfactant protein SP-H enhances the phagocytosis efficiency of macrophage-like cell lines U937 and MH-S - Diler, Ebru; Schicht, Martin; Rabung, Andrea; Tschernig, Thomas; Meier, Carola; Rausch, Felix; Garreis, Fabian; Bräuer, Lars; Paulsen, Friedrich (BMC Research Notes, 2014)
Surfactant proteins (SP) secreted by alveolar type 2 cells, play an essential role in maintaining the air-liquid barrier of the lung and are also involved in the opsonisation and clearance of bacteria by phagocytes. We have recently described a novel surfactant protein, SP-H (SFTA3). Expression of SP-H was earlier demonstrated to be upregulated by LPS and negatively regulated by IL-1? and IL-23 in vitro. The influence of SP-H on phagocytosis was measured using a murine and a human phagocytic cell line and fluorescent latex beads.SP-H markedly increases phagocytosis in vitro in the murine-derived alveolar macrophage cell lines MH-S and in human-derived differentiated U937 cells.It can be assumed that SP-H is involved in regulating phagocytic activity of macrophages. SP-H is a new player in pulmonary host defence.
EVALuna2:4439

The Potential Role of SP-G as Surface Tension Regulator in Tear Film: From Molecular Simulations to Experimental Observations - Schicht, Martin; Riedlova, Kamila; Kukulka, Mercedes; Li, Wenyue; Scheer, Aurelius; Garreis, Fabian; Jacobi, Christina; Paulsen, Friedrich; Cwiklik, Lukasz; Bräuer, Lars (International Journal of Molecular Sciences, 2022)
The ocular surface is in constant interaction with the environment and with numerous pathogens. Therefore, complex mechanisms such as a stable tear film and local immune defense mechanisms are required to protect the eye. This study describes the detection, characterization, and putative role of surfactant protein G (SP-G/SFTA2) with respect to wound healing and surface activity. Bioinformatic, biochemical, and immunological methods were combined to elucidate the role of SP-G in tear film. The results show the presence of SP-G in ocular surface tissues and tear film (TF). Increased expression of SP-G was demonstrated in TF of patients with dry eye disease (DED). Addition of recombinant SP-G in combination with lipids led to an accelerated wound healing of human corneal cells as well as to a reduction of TF surface tension. Molecular modeling of TF suggest that SP-G may regulate tear film surface tension and improve its stability through specific interactions with lipids components of the tear film. In conclusion, SP-G is an ocular surface protein with putative wound healing properties that can also reduce the surface tension of the tear film.
CRIS-Team WoS Importer:2022-06-10

Unraveling the Local Relation Between Tissue Composition and Human Brain Mechanics Through Machine Learning - Linka, Kevin; Reiter, Nina; Würges, Jasmin; Schicht, Martin; Cyron, Christian J.; Paulsen, Friedrich; Budday, Silvia; Bräuer, Lars (Frontiers in Bioengineering and Biotechnology, 2021)
The regional mechanical properties of brain tissue are not only key in the context of brain injury and its vulnerability towards mechanical loads, but also affect the behavior and functionality of brain cells. Due to the extremely soft nature of brain tissue, its mechanical characterization is challenging. The response to loading depends on length and time scales and is characterized by nonlinearity, compression-tension asymmetry, conditioning, and stress relaxation. In addition, the regional heterogeneity–both in mechanics and microstructure–complicates the comprehensive understanding of local tissue properties and its relation to the underlying microstructure. Here, we combine large-strain biomechanical tests with enzyme-linked immunosorbent assays (ELISA) and develop an extended type of constitutive artificial neural networks (CANNs) that can account for viscoelastic effects. We show that our viscoelastic constitutive artificial neural network is able to describe the tissue response in different brain regions and quantify the relevance of different cellular and extracellular components for time-independent (nonlinearity, compression-tension-asymmetry) and time-dependent (hysteresis, conditioning, stress relaxation) tissue mechanics, respectively. Our results suggest that the content of the extracellular matrix protein fibronectin is highly relevant for both the quasi-elastic behavior and viscoelastic effects of brain tissue. While the quasi-elastic response seems to be largely controlled by extracellular matrix proteins from the basement membrane, cellular components have a higher relevance for the viscoelastic response. Our findings advance our understanding of microstructure - mechanics relations in human brain tissue and are valuable to further advance predictive material models for finite element simulations or to design biomaterials for tissue engineering and 3D printing applications.
Keywords: human brain; viscoelasticity; constitutive modeling; microstructure; mechanical properties; artificial neural network; extracellular matrix

Updated incidence of dry eye syndrome in Germany - Posa, A.; Sel, S.; Dietz, R.; Sander, R.; Bräuer, Lars; Paulsen, Friedrich (Klinische Monatsblätter für Augenheilkunde, 2014)
Dry eye is one of the most common eye surface disorders. Patients suffer in particular from annoying subjective symptoms that compromise quality of life. The aim of the study was to find out when patients consult ophthalmologists in Germany and what symptoms they present.170 patients treated at ophthalmological practices in Bavaria, Saxony and Saxony-Anhalt with dry eye were surveyed regarding their symptoms.The majority of those questioned were 40 years of age or older (88 %) (average: 60), female (59 %) and described a variety of subjective symptoms (65 %). More than five different concurrent symptoms were named. There is a recognisable increase in cases - by more than 3.5 times - at the age of forty (in women) and fifty (in men).We hope to contribute with the data obtained to a more complete understanding of this highly complex pathological process. A further aim is to facilitate recognition of this mostly chronic condition in its early stages when the symptoms are still poorly defined. The data on the German population obtained here should become part of a comparative analysis within the international context. Despite considerable scientific effort, dry eye remains a difficult challenge for both patients and attending physicians.
EVALuna2:4437